Navigating the Postmodern Landscape: Embracing Interdisciplinary Openness in Pastoral Theology - Ganc, Damijan (Verbum Vitae, 2024)
In the face of rising secularization and the waning influence of the Church, contemporary pastoral theology encounters both a formidable challenge and an enticing opportunity in the postmodern era. This article explores how enhanced interdisciplinary engagement of pastoral theology can foster a renewed approach to evangelization aligned with contemporary sensibilities. Through a comprehensive literature review, we shed light on the experiences of the postmodern individual. By applying the analogy method and anchoring the concepts of “Logos Spermaticos” and “Influence and Vulnerability” in pastoral theology, we reveal its potential contribution to the interdisciplinary evolution of the concept of universal fraternity. The analysis shows that interdisciplinary collaboration in pastoral theology unfolds developmental prospects on two levels – learning from and learning with other disciplines. The “Logos Spermaticos” concept underscores the importance of acquiring new skills, empowering pastoral workers to communicate Christian doctrine more effectively. Simultaneously, the “Influence and Vulnerability” concept fosters a dialogical approach, positioning pastoral theology as a respected interlocutor in contemporary interdisciplinary dialogues. Collaborative efforts with other disciplines empower pastoral theology to foster dialogue and deepen the idea of universal fraternity, both in academic discourse and practical application. The interdisciplinary and global development of fraternal humanism represents the necessary “loosening of the soil” for the seed of the Word of God to sprout in the future. Therefore, it becomes imperative for pastoral theology to transcend its conventional role, actively engaging in interdisciplinary dialogue, thereby charting a course toward an elevated societal role and innovative avenues for proclaiming the Gospel.